Use of acetylsalicylic acid, expression of pre-eclâmpsia markers and doppler of uterine arteries in the second gestational trimester (Research, Society and Development, 2025)
Preeclampsia (PE) occurs during pregnancy with hypertension and proteinuria and is associated with maternal and fetal morbidity and mortality. In the pathophysiology, there is a vascular and placental inflammatory dysfunction, altering serum and biophysical markers. Acetylsalicylic acid (ASA) can prevent the disease by reducing the inflammatory process. Thus, the aim of this study was to analyze whether the use of ASA interferes with the Doppler of the uterine arteries and serum markers of PE in pregnant women. This was a cross-sectional study involving 71 pregnant women between 20 and 24 weeks and 6 days of gestation, in maternity hospitals in Rio Grande do Norte. Questionnaires were applied to characterize the population; morphological ultrasound was performed in the 2nd trimester with Doppler evaluation of the uterine arteries and measurement of serum levels of PlGF (Placental Growth Factor). The data were tabulated in SPSS (Statistical Package for the Social Sciences – version 4.2.2) for descriptive analysis and Spearman correlation. The mean body mass index (BMI) of the sample was 31.02. Thirty-eight pregnant women confirmed the use of AAS and in this group the mean values of the pulsatility index (PI) of the uterine arteries were 1.03 and of the PlGF 307.80, and in those who did not use, the values were 0.95 and 325.3, respectively. In this study, the use of AAS did not contribute to the reduction of the PI of the uterine arteries and there was no significant difference in the mean of the PIGF. Larger studies are important to confirm these results.